Water Quality of the Sail River, Pekanbaru Based on Type and Population of Macrozoobenthos - Muharisa '; Adriman '; Nur El Fajri (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
Sail River is one of the most polluted river in Pekanbaru. A study aims to understand the physical, chemical and biological condition of water quality in the river was conducted from February to Mai 2015. The biological condition of the water was analyzed based on type and population of macrozoobenthos present in the river. Parameters measured were temperature, depth, transparency, turbidity, current speed, TSS, pH, DO, BOD, COD, nitrate and phosphate content. Data were analyzed using the NFS-WQI and FBI method. Results shown that the macrozoobenthos present in the Sail river were consisted of 3 phylum and 6 family, namely Annelid (Tubificidae), Arthropod (Chironomidae), and Mollusks (Ampullidae, Bithyniidae/ Bulimidae, Thiaridae). The water quality parameters in the Sail River are as follow: temperature 29-30oC, depth 0.21-0.56 m, transparency 6.45-15.27 cm, turbidity 112-593 NTU, current speed 8.08-26.58 cm/s, TSS 44.00-173.67 mg/L, pH 5-6, DO 2.80-11.51 mg/L, BOD5 4.77-29.12 mg/L, COD 10.67-44.80 mg/L, nitrate 0.18-0.81 mg/L and phosphate 1.06-1.71 mg/L. Based on NSF-WQI result, the water quality in the Sail River was categorized as poor to very poor (27.97-14.68), while the FBI value (8-8.72) indicates that the river was badly contaminated.Keyword: Sail River, water quality, NSF-WQI, Family Biotic Index, Macrozoobenthos